ANALISIS KINERJA KOPERASI MELALUI PEMERINGKATAN KOPERASI BERDASARKAN PERMENKOP NO. 21/PER/M.KUKM/IX/2015 - Reslianty Rachim; Zulkifli (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2022)
Rating is one of the performance assessments of cooperatives. To find out the ranking of the all-round business cooperative of the noble servant of Kutai Kartanegara Regency in 2021 is the goal of this study. The assessment is based on PERMENKOP and SMEs of the Republic of Indonesia Number 21/Per/M.KUKM/IX/2015 concerning Cooperative Assessment. This research is an evaluation research. The types of data used in this study are qualitative and quantitative data, the data sources in this study are primary and secondary. The subjects of this study were administrators, supervisors, members of KSU ABDI LUHUR, Kutai Kartanegara Regency. The object of this research is the ranking of KSU Abdi Luhur. Data collection techniques using interview techniques, documentation and questionnaires. The assessment uses ranking as an Evaluation Model. This study shows that: From the institutional aspect 495, the business aspect 75, the financial aspect of the cooperative 25, the cooperative benefit aspect 40 and for the community 25 with a total assessment of 860 ABB predicate (Quality Enough)